Bylaws as complementary means of tenure security and management of resources conflicts: synthesis of various West African experiences. Issue 2 (2nd April 2016) - Alinon, Koffi; Kalinganire, Antoine
Abstract: Land tenure issues are the cornerstones of efforts to address sustainable development in West Africa. Lack of tenure security is still creating an unstable and conflictual context that threatens individual investments in agroforestry. In order to minimize conflicts over land, various sets of tools have been experimented over time in different parts of the region. This paper briefly reviews the different systems for securing access to land and for avoiding conflicts over natural resources. It then focuses on the recent emergence of bylaws and local conventions in the management of natural resources in French West Africa. Where official regulations on local shared resources suffer from limited enforcement, populations continue, through their traditional representatives, to engage in the negotiation of bylaws and local conventions for the management of natural resources. The paper ends with exploring further steps toward formal endorsement of bylaws and local conventions as tools for preventing and better managing land-based conflicts.